2005
DOI: 10.2527/2005.8361455x
|View full text |Cite
|
Sign up to set email alerts
|

Prion biology relevant to bovine spongiform encephalopathy1

Abstract: Bovine spongiform encephalopathy (BSE) and chronic wasting disease (CWD) of deer and elk are a threat to agriculture and natural resources, as well as a human health concern. Both diseases are transmissible spongiform encephalopathies (TSE), or prion diseases, caused by autocatalytic conversion of endogenously encoded prion protein (PrP) to an abnormal, neurotoxic conformation designated PrPsc. Most mammalian species are susceptible to TSE, which, despite a range of species-linked names, is caused by a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 172 publications
0
50
0
3
Order By: Relevance
“…Given the resilience of the infectious prion [23], the relative ease of transmission [24], and the uncertain interspecific barrier to transmission [25–27], a response plan is necessary as more is learned about the health and economic impacts of CWD. Therefore, management has primarily focused on containment utilizing various combinations of expanded surveillance, restrictions on movement or translocation of susceptible individuals, public hunting, and culling by government agencies [4,28–31].…”
Section: Introductionmentioning
confidence: 99%
“…Given the resilience of the infectious prion [23], the relative ease of transmission [24], and the uncertain interspecific barrier to transmission [25–27], a response plan is necessary as more is learned about the health and economic impacts of CWD. Therefore, management has primarily focused on containment utilizing various combinations of expanded surveillance, restrictions on movement or translocation of susceptible individuals, public hunting, and culling by government agencies [4,28–31].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental transmission of bovine spongiform encephalopathy to sheep has been demonstrated, but the low prion level in non-nervous tissues (i.e. gut) in litter and the low probability of cross-species infection represent minimal risk of animal excreta as source of transmissible prion disease (Novakofski et al, 2005). Therefore, the objective of this study was to evaluate in lambs the nutritional value of total mixed rations with maize stover silage fortified with pig excreta, poultry litter or urea as N sources, and with molasses or bakery by-products as energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This resistance results in the accumulation of the non-degraded form of the protein which results in the neural degeneration and spongiform appearance of infected CNS tissues. 4 In classical BSE, the pathogenesis of the disease is the result of the transference of the infectious prion from the digestive tract into the peripheral nervous system and then to the brain. 5 Studies of the pathogenesis have concluded that the route of transmission is from the ileal Peyer's patches and the tonsils through the parasympathetic and sympathetic nerve fibers of the autonomous nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…3 TSEs are unique in that they may be genetic, sporadic or transmitted but, in all cases the disease state is associated with accumulation of the abnormal PrP Res in the brain and central nervous system (CNS) causing degeneration. 4 Classical BSE is a form of TSE acquired by the consumption of meat and/or bone meal contaminated with the (PrP Res ) or infectious prion agent 5 and was first observed in the United Kingdom (UK) in 1986. 6 A large number of infected animals entered the food chain in the preclinical state and were consumed by the human population in the UK and elsewhere.…”
Section: Introductionmentioning
confidence: 99%